Phase, foundation and problems: development of elite sports in China - Zheng, G.; Zu, Q.; Xiong, X. (BioTechnology: An Indian Journal, 2014)
Elite sports in China is gradually forming on the basis of keeping solving the problems inpractice and making responding choices according to the actual requirements at that time, while it has not the prior "Empirical Model" on the whole originally. Therefore, in a sense, its formation and evolution are constantly exploring the process of actual selections that is suitable for the development of our society. However, historical experience tells us that only if model of sports development maintains relative consistency with the model of social development, sports development could realize the real development. Therefore, the mode of elite sports development that adapts the socialist market economic system cannot be limited to simple repair of the existing system (or mode), and it must foot one stablishing a mode of elite sports development that conforms to China's current social realities while converging with developing direction of China's social reform.